The Governance and Tourism: A Case of Developing Countries - Khan, Rana Ejaz Ali; Ahmad, Tusawar Iftikhar; Haleem, Jaweria (Asian Journal of Economic Modelling, 2021)
Tourism is a rapidly growing industry globally and it is contributing a significant part in the GDP of the economies. In the literature, a variety of determinants of tourism are discussed theoretically and empirically but the effect of national governance on tourism is rarely discussed. This study investigates the effect of governance on tourism development in a panel of 65 developing economies for the time period of 2000-2015. Tourism development is measured by an index of three components, i.e. spending by international tourists, spending by local tourists and tourism’s share in total employment in the economy. For governance an index is constructed based on indicators of government effectiveness, political stability, regulatory quality, rule of law, and voice and accountability. Data has been taken from World Development Indicators (WDI), Worldwide Governance Indicators (WGI) and World Travel and Tourism Council (WTTC). Generalized Method of Moment (GMM) estimation indicates that governance positively influence tourism development and its components, i.e. foreign visitors spending, domestic tourist spending and contribution of tourism in employment. The indicators of governance, i.e. government effectiveness, political stability, regulatory quality, rule of law and voice and accountability also positively affect tourism development. Terrorism, environmental degradation and corruption have shown adverse effect on tourism development as well as components of tourism development. The economic growth and trade openness have encouraging effect on tourism development and its comments. It is concluded that through good governance tourism may be developed but terrorism and corruption are needed to be eliminated.